Evolution of the oral discourse in students of Spanish and Spanish Language of the Universidad Industrial de Santader as unit of identity of the oral bumangues speech - Gómez Díaz, Adrián
An approximation sociolinguistic of exploratory character to the study of the scoreboards of the speech in the speech of the students in Master in Spanish and Literature and Master in Basic Education in Castilian Language of the Industrial University of Santander located in Bucaramanga city demonstrates the relation that exists in the use of the above mentioned scoreboards and the university level of these students. The study took the use as an approach in the narrative oral speech of the informants concluding that And, That, Eh, so, Like, But, Then, When, Because were preferred in the speech of most of the university population, whereas it was demonstrated if really existed or not a favorable evolution in this speech and the use of scoreboards. There is demonstrate, that certainly there is a favorable evolution, but in a very brief and slow way, specially, in the variety of the scoreboards as read-writer is advanced in the different levels due to the factor and to the accompaniment of the teachers as regulatory entities. Equally, the study throws the difficulties that the speakers present in the use of the scoreboards and the problems that the students face on having used them. Everything previous, with ride to determining that the use of these discursive scoreboards they are the elements most used in the oral speech of the students of these two university programs. Likewise, there is demonstrate that some typical features exist in the oral narrative of the students who are relate with the sub dialect of Santanderes and the linguistic aspects of the speech in Bucaramanga. Concluding that the variability of the scoreboards in the oral speech of the students corroborates the dynamism of the language and the importance of the factors sociolinguistics as causative of this process.